Peran Tenaga Kesehatan dalam Kesiapsiagaan Menghadapi Bencanan Banjir di Kota Lhoksemawe - Anda Syahputra; Abdurrahman Abdurrahman; Marlina Marlina; Jamil Fauzi (Malahayati Nursing Journal, 2023)
ABSTRACT The territory of the Unitary State of the Republic of Indonesia has geographical, geological, hydrological and demographic conditions that are prone to disasters. Lhoksemawe City is a city that often experiences floods every year, and almost half of Lhoksemawe city area experiences floods. The role of health workers is important for preparedness in dealing with flood disasters. Health workers have a big role in dealing with flood disasters, especially in terms of health.To find out the role of health workers in preparedness for flood disasters.The design of this research is descriptive analytic with a cross sectional research design. The population in this study were all health workers in Lhoksemawe City. The sample of this study was 30 people using proposive sampling technique. Data analysis technique using chi square test.The role of health workers who are ready to face flood disasters is 86.9%. The results of statistical tests using chi square obtained a sig value of 0.03 so it can be concluded that there is a relationship between the role of health workers and preparedness in dealing with floods. It can be concluded that there is a relationship between the role of health workers and preparedness in dealing with flood disasters. Keywords: The Role of Health Workers, Preparedness, Flood Disaster  ABSTRAK Wilayah Negara Kesatuan Republik Indonesia memiliki kondisi geografis, geologis, hidrologis, dan demografis yang rawan bencana. Kota Lhoksemawe merupakan kota yang sering terjadi bencana banjir disetiap tahunnya, dan hampir setengah wilayah kota lhoksemawe mengalami bencana banjir. Peran tenaga kesehatan penting untuk kesiapsiagaan dalam mengahadapi bencana banjir. Tenaga kesehatan memiliki peran yang besar dalam menangani bencana banjir khususnya dalam hal kesehatan. Tujuan penelitian untuk mengetahui peran tenaga kesehatan dalam kesiapsiagaan menghadapi bencanan banjir. Desain penelitian ini deskriptif analitik dengan rancangan penelitian cross sectioal. Populasi pada penelitian ini seluruh tenaga kesehatan di Kota Lhoksemawe, Sampel penelitian adalah 30 orang dengan menggunakan tehnik proposive sampling. Tehnik analisa data menggunakan uji chi square. Peran tenaga kesehatan siap dalam menghadapi bencana banjir sebesar 86,9%. Hasil Uji Statistik mengunakan  chi square  didapatkan nilai sig 0,03  maka dapat disimpulkan ada hubungan peran tenaga kesahatan dengan kesiapsiagaan dalam menghadapi bencana banjir.  Dapat disimpulkan ada hubungan peran tenaga kesahatan dengan kesiapsiagaan dalam menghadapi bencana banjir. Kata Kunci: Peran Tenaga Kesehatan, Kesiapsiagaan, Bencana Banjir